Implementasi Lesson Study Dalam Program PPL Untuk Meningkatkan Keaktifan, Hasil Belajar Siswa, dan Kompetensi Calon Guru - Inna Al Ma’aritj; Puji Rahayu; Novita Dewi (Jurnal Pendidikan Dirgantara, 2025)
This study explores the implementation of Lesson Study within the teaching practicum (PPL) program to enhance student engagement, learning outcomes, and the teaching competencies of pre-service teachers. Employing a Classroom Action Research (CAR) approach, the research was conducted in three cycles involving second-grade students at UPT SD Negeri Latsari. Each cycle consisted of the Lesson Study stages: planning, execution, and reflection. The findings indicate significant improvements in all targeted areas. Student engagement showed a steady increase, starting from 63% in Cycle 1 and reaching 91% in Cycle 3, supported by interactive strategies such as group worksheets, flipbook media, and the Team Games Tournament (TGT) model. Correspondingly, learning outcomes improved, with average test scores rising from 68.2 in Cycle 1 to 83.7 in Cycle 3. Furthermore, pre-service teachers demonstrated notable development in key teaching competencies, particularly in lesson planning, classroom management, and reflective practices. Overall, the study underscores the effectiveness of Lesson Study in promoting collaborative teaching practices, improving the quality of instruction, and fostering professional growth among pre-service teachers. The integration of innovative and interactive learning strategies within the Lesson Study framework contributed significantly to creating a more engaging and impactful learning environment for students.